Studi Empiris tentang Pengaruh Beban Kerja, Insentif, dan Konsekuensi terhadap Peningkatan Kinerja Karyawan - Bustam; Heslina (LPPM STIEM, 2025)
: In this era of globalization, companies are in great need of competent and high-quality human resources. Every company must be prepared to adapt and enhance itself to compete and overcome all challenges in the future. This research aims to determine the Influence of Workload, Incentives, and Consequences on Employee Performance in the Makassar City Water Supply Company (PDAM). This research adopts a quantitative research approach. The sample to be examined consists of 62 employees in the Makassar City Water Supply Company, selected using the purposive sampling technique. Data for this research were obtained through questionnaire distribution. Data analysis was conducted by testing instruments, classic assumption tests, multiple regression analysis, and hypothesis testing using the SPSS 26 application. The results of this research indicate that the Workload variable (X1) has a significant positive effect on employee performance (Y), the Incentive variable (X2) has a positive and significant effect on employee performance (Y), and the Consequences variable (X3) does not have a significant effect on employee performance (Y).